AVALIAÇÃO DE MODELOS APLICADOS À PREDIÇÃO DA ESTABILIDADE E COMPATIBILIDADE DE PETRÓLEOS - Moura, Lyzette Gonçalves Moraes de (2007)
In this work, among the main models developed and applied for pure crude oils stability prediction and for the compatibility between crude oils/fractions; the Toluene Equivalence (TE) performance, the Heithaus parameter (Parameter P) of the crude compatibility model, the Crude Compatibility Model, the Colloidal Instability Index (CII) and the one of the Bureau of Mines Correlation Index - Toluene Equivalence (BMCI-TE) were valuated. For their implementation, except the CII, is necessary the determination of the asphaltenes precipitation onset, obtained by adding n-heptane to the pure crude until the occurrence of precipitation. It was not possible to get that measurement in part of the estimated crude oils; due to that fact we were unable to analyze the model efficiency for these samples stability/compatibility. The CII results refer to the total number of samples, but the rest refer only to those presenting precipitation when added with n-heptane end their mixtures. In the stability evaluation, the TE furnished only a stability order related classification, while with the P parameter it was attained 89% of prediction target hitting; with the Crude Compatibility Model together with the BMCI-TE, the prediction target hitting was 95%, whereas with the CII the prediction target hitting was 3%. With respect to mixture compatibility the TE, P parameter and the Crude Compatibility Model revealed 83% of the prediction target hitting, and in the BMCI-TE the prediction target hitting 50%. The CII presented 39% prediction target hitting for binary mixtures and for ternary mixtures, which could only be evaluated according to this parameter, the prediction target hitting was 80%. Except the CII, the parameters presented as main limitation the impossibility of its application to systems involving samples that do not precipitate when added with n-heptane; but the CII, which does not have this relation, revealed the worst performance. Classical models of stability and compatibility of crude oils proved to be little efficient for analyzing systems that include the Brazilian crude oils considered in this study, This strongly suggests the necessity of deeper studies to enhance the already existing models and indices or to develop new ones.